Rotavirus vaccination - V. K. Tatochenko (Медицинский совет, 2016)
Rotavirus (RV) infection (RVI) which causes acute gastroenteritis (RVGE) is among the most common infectious diseases in children in both developing and developed countries. Before the name RV was invented, the disease was designated as “toxic dyspepsia”, “our cholera” - “cholera nostra”. According to the WHO, in 2008 RV caused 453 thousand children’s deaths worldwide, mostly in the developing countries; RV mortality is 80 per 100 thousand. Annually, at least 2 million children are admitted to hospitals with RVGE; according to data from 35 countries, RV causes 40% (34–45%) of all diarrhea [1].